2022
DOI: 10.1002/apj.2846
|View full text |Cite
|
Sign up to set email alerts
|

Performance of minerals and crystallization properties of synthetic slags with various CaO/MgO in slagging gasifiers

Abstract: The fluidity of coal ash slag at high temperatures is an important factor that determines its applicability and operating conditions in entrained flow gasification. In this study, six synthetic slags with different CaO/MgO rations were prepared to study their effect on slag fluidity. The results showed that the flow temperature of slags decreased first and then increased with the decrease of CaO/MgO ratio. When the slag had a high or low CaO/MgO ratio, or when the contents of CaO and MgO in the slag were simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Therefore, the depolymerization ability of CaO is an important factor affecting the slag viscosity and melting temperature. 9,10 All the above-mentioned studies have shown that the melting temperature of coal ash can be reduced when the content of MgO is within a certain range. However, although most studies examined the macroscopic influence of MgO on the melting characteristics of coal ash, there is still a lack of research analyzing its microscopic impact on the melting temperature of coal ash.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the depolymerization ability of CaO is an important factor affecting the slag viscosity and melting temperature. 9,10 All the above-mentioned studies have shown that the melting temperature of coal ash can be reduced when the content of MgO is within a certain range. However, although most studies examined the macroscopic influence of MgO on the melting characteristics of coal ash, there is still a lack of research analyzing its microscopic impact on the melting temperature of coal ash.…”
Section: Introductionmentioning
confidence: 99%